Differentiation of thymocytes from CD3-CD4-CD8- through CD3-CD4-CD8+ into more mature stages induced by a thymic stromal cell clone. - Tatsumi, Y (1990)
We have investigated the capacity of our established thymic stromal cell clone (MRL104.8a) or its derived factor(s) to induce the differentiation of immature thymocytes. Culture of purified adult murine double-negative (CD4-CD8-, indicated here as CD4-8-) thymocytes on the MRL104.8a thymic stromal cell monolayer for 1 day resulted in the induction of an appreciable percentage of CD4-8+ thymocytes. A bone marrow-derived stromal cell monolayer or a L929 fibroblast monolayer failed to generate CD4-8+ cells. This differentiation could also be induced by a semipurified sample of the MRL104.8a culture supernatant, which contained a thymic stroma-derived T-cell growth factor capable of contributing to the growth of double-negative immature thymocytes. CD4-8+ thymocytes generated 1 day after coculture with the MRL104.8a cells or the sample containing thymic stroma-derived T-cell growth factor were found to be CD3- and J11d+, excluding the possibility of expansion of mature (CD3+4-8+) thymocytes present in the thymus. More importantly, when the culture period was extended to 2 or 3 days, an appreciable number of CD4+8+ and single-positive (CD4+) cells were generated on the MRL104.8a monolayer. Thus, these results provide the direct demonstration that CD3-4-8- immature thymocytes are promoted to differentiate through a rapidly cycling intermediate (CD3-4-8+) into double- and single-positive cells by a specialized thymic stromal component.